Biocaiv: an integrative webserver for motif-based clustering analysis and interactive visualization of biological networks - Dong-Xu Li; Peng Zhou; Bo-Wei Zhao; Xiao-Rui Su; Guo-Dong Li; Jun Zhang; Peng-Wei Hu; Lun Hu (BMC Bioinformatics, 2023)
Abstract Background As an important task in bioinformatics, clustering analysis plays a critical role in understanding the functional mechanisms of many complex biological systems, which can be modeled as biological networks. The purpose of clustering analysis in biological networks is to identify functional modules of interest, but there is a lack of online clustering tools that visualize biological networks and provide in-depth biological analysis for discovered clusters. Results Here we present BioCAIV, a novel webserver dedicated to maximize its accessibility and applicability on the clustering analysis of biological networks. This, together with its user-friendly interface, assists biological researchers to perform an accurate clustering analysis for biological networks and identify functionally significant modules for further assessment. Conclusions BioCAIV is an efficient clustering analysis webserver designed for a variety of biological networks. BioCAIV is freely available without registration requirements at http://bioinformatics.tianshanzw.cn:8888/BioCAIV/ .